Return of Benefit to Society of Publicly Funded Innovations to Combat COVID-19. (7th December 2021) - Yu, Helen
In response to the COVID-19 pandemic, significant public funds have been invested worldwide into the research, development, and manufacturing of pharmaceutical products to combat the novel coronavirus. Traditionally, intellectual property (IP) rights have been justified in the pharmaceutical sector because of the time and cost associated with drug discovery and development. However, if (a) the cost of research for COVID-19 related innovations have largely been subsidized by the public through public research grants; (b) the time for development has been significantly reduced through publicly funded initiatives; and (c) manufacturing has been de-risked through taxpayer funded advance purchase agreements, should IP rights be asserted on innovations that have largely already been paid for by the public?. There needs to be clear legal and regulatory frameworks, informed by policy objectives such as principles of "responsible research and innovation" and "global public good, " to ensure that outcomes of publicly funded efforts can ultimately reach the intended public. Without any access and production conditions associated with the use of public efforts, worldwide supplies to medical solutions that benefited from these public initiatives can be frustrated. This article proposes a legal framework to address future access and availability problems to medical innovations that benefit from publicly funded initiatives.